A case of hypopituitarism accompanying Kearns–Sayre syndrome treated with human chorionic gonadotropin: A case report and literature review. (6th October 2016) - Kang, Y.‐X.; Wang, Y.‐J.; Zhang, Q.; Pang, X.‐H.; Gu, W.
Summary: Kearns–Sayre syndrome (KSS) is a disorder caused by mutations in mitochondrial DNA. Here, we report an unusual case of Kearns–Sayre syndrome accompanied by hypopituitarism (deficiencies in reproductive and growth hormones). A 20‐year‐old male presented with growth retardation for the last 8 years, as well as the following findings: short stature, delayed puberty, myasthenia, an extraocular movement deficit, drooping eyelids, pectus carinatum and scoliosis. Cerebral enhanced magnetic resonance imaging revealed dysplasias of the pituitary, white matter and cerebellum. Laboratory work‐up showed subnormal testosterone and growth hormone levels, a subnormal testicular volume, sensorineural deafness, pigmentary retinopathy, complete right bundle branch block and left anterior bundle branch block. Pathological examination revealed ragged red muscle fibres. Thus, this rare case involved the coexistence of Kearns–Sayre syndrome and hypopituitarism in a patient. Administration of coenzyme Q10 for the KSS and hormone replacement therapy for the endocrinopathies were performed for treatment of this patient.